Invariant subspaces, exact solutions and stability analysis of nonlinear water wave equations - Hosseini, K.; İnç, Mustafa; Shafiee, M.; Ilie, M.; Shafaroody, A.; Yusuf, A.; Bayram, M. (Elsevier, 2020)
The key purpose of the present research is to derive the exact solutions of nonlinear water wave equations (NLWWEs) in oceans through the invariant subspace scheme (ISS). In this respect, the NLWWEs which describe specific nonlinear waves are converted to a number of systems of ordinary differential equations (ODEs) such that the resulting systems can be efficiently handled by computer algebra systems. As an accomplishment, the performance of the well-designed ISS in extracting a group of exact solutions is formally confirmed. In the end, the stability analysis for the NLWWE is investigated through the linear stability scheme. (C) 2019 Shanghai Jiaotong University. Published by Elsevier B.V.
Keywords: Nonlinear water wave equations; Invariant subspace scheme; Exact solutions; Stability analysis